Pengaruh Kualitas Pelayanan dan Promosi Terhadap Keputusan Pembelian pada Minimarket Alfamart Sahid Sudirman, Jakarta Pusat - Azzah, Aini; Ety Nurhayaty (PT. Karya Inovatif Nusantara, 2025)
Competition in the retail business in Indonesia is getting tougher. To stay competitive, retail businesses must ensure that they always provide good service to remain the choice of consumers. This study aims to analyze whether service quality and promotion have an influence on consumer purchasing decisions at Minimarket Alfamart Sahid Sudirman. This research uses quantitative methods. The population in this study were consumers of Alfamart Sahid Sudirman, the research sample consisted of 100 respondents selected using random sampling technique. Data collection was carried out using a questionnaire, while data analysis was carried out using multiple linear regression methods assisted by SPSS version 26.Based on the results of this study that service quality partially has a positive and significant effect on purchasing decisions, promotion partially has a positive and significant effect on purchasing decisions. Service quality and promotion simultaneously influence purchasing decisions at Alfamart Sahid Sudirman Minimarket, Central Jakarta. Thus, it can be concluded that service quality and promotion have a significant influence, both partially and simultaneously on consumer purchasing decisions at Minimarket Alfamart Sahid Sudriman, Central Jakarta